PREGNANCY DANGER SCREENING WITH KARTU SKOR POEDJI ROCHJATI (KSPR) - Zakkiyatus Zainiyah; Iin Setiawati; Eny Susanti (STIKES NGUDIA HUSADA MADURA, 2020)
Danger signs in pregnancy are symptomatic signs that indicate the mother or baby is in danger. If there are signs of danger, usually the mother needs to get immediate help in the hospital (hospital emergency). Most pregnancies end in normal labor and the puerperium. However, 15 to 20 out of 100 pregnant women experience problems with pregnancy, childbirth or childbirth.This community service is carried out by providing counseling or providing directions on how to screen for danger signs using the KSPR which has been rarely used so far because there is a KIA book, by knowing the information on pregnancy danger signs, it is hoped that pregnant women will understand the danger signs of pregnancy. In addition to holding outreach, also conducting early detection of preeclampsia through IMT, ROT and MAP, besides conducting interviews through questionnaires by asking about the characteristics of pregnant women in Kelbung Village, Sepuluh, Bangkalan.